An Analysis of Students' Writing Skill Taught by Project-Based Learning Model at the Tenth Grade of SMK Negeri 1 Dharma Caraka Gunungsitoli Selatan in 2022/2023 - Ice Trisna G Zega; Hidayati Daeli; Afore Tahir Harefa; Yaredi Waruwu (Universitas Muhammadiyah Enrekang, 2023)
The researcher conducted a study entitled An Analysis of Students' Writing Skill Taught by Project-Based Learning Model at the Tenth Grade of SMK Negeri 1 Dharma Caraka Gunungsitoli Selatan in 2022/2023, with the aim to find and describe students' writing skill and the problems faced by students in writing taught by project-based learning model at the Tenth Grade of SMK Negeri 1 Dharma Caraka Gunungsitoli Selatan in 2022/2023. This research had conducted using descriptive qualitative research method. The data was collected and analyzed using the Miles and Huberman (1984) data analysis model. The results of the study showed that there were 12% or 4 students got the excellent category, there were 58% or 19 students got the good category, there were 15% or 5 students got the average category, there were 15% or 5 students got the fair category. Meanwhile, the average writing skill of students of class X Askep 2 SMK Negeri 1 Dharma Caraka Gunungsitoli Selatan who were taught using a project-based learning model were good with an average of 65.27, which meant that students had written descriptive text according to the form but still incomplete, less organized but the main idea is already visible, the choice of words and expressions is sometimes less precise but does not interfere with the meaning, and there are some mistakes in spelling but the meaning is not blurred. Meanwhile, the problems that students often encountered when writing English texts were cognitive problems consisting of generic structure, grammar, and spelling problems.